Wavelenght Division Multiplexing Applications in Optical Communication Systems - Boz, Irem; Unverdi, N. Ozlem (IEEE, 2013)
In this study, first, the principles of Wavelength Division Multiplexing systems, WDM systems, which are the most preferred systems in optical communications today, are introduced and the effect of the length of the optical fiber on system performance is studied In the second system designed, the effect of the number of channels and the use of erbium doped fiber amplifier, EDFA, on wavelength division multiplexing is investigated. Optical communication systems suitable for this study are analysed with OptiSystem 11.0 simulation program The electrical signal is transmitted after being converted into an optical signal form in the first system tested, and is compared with Bit Error Rate, BER, analysis after being returned into electrical form at the receiver. It is observed that increasing the length of the transmission line causes a decrease in the performance of the optical communication system In the second system tested, it is determined that the amplification characteristics change depending on the number of channels present.
Keywords: Communication technolohgies; optical communications; wavelenght division multiplexing; erbium doped fiber amplifier; bit error rate; Engineering; Telecommunications